(untitled) (Homoeopathy for All, 2026)
This case report describes the successful Homoeopathic management of a known case of COPD along with severe Restrictive Pathology diagnosed through Pulmonary Function Test, in a 74year-old male patient using Kalium carbonicum 200CH. The patient presented with complaints of cough and shortness of breath for the past 2 years. After administration of Kali carb 200C, the patient showed significant improvement in symptoms. Improvement noticed in the values of PFT as well. Modified Naranjo Criteria for Homoeopathy (MONARCH) was used, which showed significant causal attribution. Symptoms, before and after the treatment are assessed using the COPD Assessment Test (CAT) scale and mMRC Dyspnoea Severity scale, which showed marked improvement. Investigation reports of Pulmonary Function Tests was taken as objective evidence after obtaining consent from the patient. The case reporting is done according to the HOM-CASE guidelines, extension of CARE guidelines.